The Role of Parents in the Development of Early Childhood Speech Acts - Andi Nurhayati; Harmita Sari; Husnani Aliah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
The aim of this research is to find out the role of parents in influencing the development of speech acts in early childhood. This research uses qualitative methods, namely research that uses observation, interviews and documentation techniques starting from data collection to interpretation. This research is analytical observational research, the research paradigm used is the role of parents in the development of early childhood speech acts. The types of data used are primary data and secondary data. The role of parents in the development of early childhood speech acts is very important for their development, because parents are the first and main environment for their children. early childhood development through speech act training carried out by parents in a directed, planned and continuous manner. The relationship between children and their parents has an influence on the development of children's speech acts.